Prevalence of face mask-induced dry eye and ocular irritation amid COVID-19 among health workers in Jazan - Al-Ibrahim, Ahmed Ibrahim; Alagsam, Abdulaziz Ali; Mohammed Abulqusim, Ebrahim; Ng, Yee Guan; Abualqasim, Almothana Makki; Mohammed Hamdi, Sulaiman; Hakami, Faisal Hadi; Hurubi, Ahmed Yahya; Mohammed Tawashi, Manal (Dow University of Health Sciences, 2023)
Background: One of the most important defenses against the COVID-19 pandemic is the use of facemasks. Long-term facemask use can result in mask-associated dry eyes. This study explored the prevalence of face mask-associated dry eyes (MADE) and associated factors among health workers in Jazan. Methods: This prospective cross-sectional clinical study was carried out among healthcare workers (Physicians, Dentists, Pharmacists, Technicians, Nurses, and Administrative staff) who wore facemasks during duties at Prince Mohammed Bin Nair Hospital in Jazan, Sudi Arabia, from 2020 to 2022. Two hundred ninety-eight participants were randomly selected. The participants were given a questionnaire about their socio-demographic characteristics, occupational information, health information, and the duration they had used glasses, masks, and technological devices. The daily average quantity of time spent sleeping was also investigated. The severity of dry eye disease was determined using OSDI scores. The chi-square test and Fisher's exact test examined categorical variable connections. Mean differences were calculated using an independent -test. Logistic regression will discover COVID-19 severity predictors. A statistically significant P-value is . Result: Among 298 health workers in this study fulfilling the inclusion criteria. The mean age of the respondents was years old, consisting of 61.3% male and 38.7% female out of 298 respondents whom the majority of them were Saudi (89.6%) and the rest non-Saudi (10.4%). Based on the Ocular Surface Disease Index (OSDI) score, almost half of the respondents (49.0%) obtained an average score in terms of dry eye disease. Only gender and marital status were significantly associated with OSDI score and respectively). From the Health Information provided, most of the variables were significantly associated with the OSDI score. Conclusion: This study concluded that face mask-associated dry eye (MADE) prevalence among health practitioners stands at 51%, partly explaining the worsening dry eye disease symptoms among mask wearers.